PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP FINANCIAL DISTRESS - Ardina Nuresa; Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2013)
This study analyzes the impact of audit committee effectiveness on financial distress by using discriminant analysis (z-score). The effectiveness of audit committee can be seen from size of audit committee, independence of audit committee, frequency of audit committee meeting, and financial knowledge of audit committee. This study use one control variable is firm size. Population that use in this study is 603 listed manufactured firms in Indonesia Stock Exchange in 2008-2011. Based on purposive sampling method, there are 209 samples consist of 33 financially distressed firms and 176 non financially distressed firms. Financial distress criteria is measure by discriminant analysis (z-score). Data analysis using logistic regression with SPSS 16. The result show that frequency of audit committee meeeting and financial knowledge of audit committee have significant negative affect with financial distress.